Concentração do EGF na saliva de pacientes com tumores em cabeça e pescoço e sua relação com a mucosite oral. - Paiva, Monique Danyelle Emiliano Batista (2008)
The aim of this study was to assess salivary EGF concentration in head and neck cancer patients and its correlation with oral mucositis. It was an observational, transversal, control-case study. Whole stimulated saliva was collected in this groups: G1 control (n=9), G2 diagnostic moment (n=13), G3 before therapy (n=11), G4 during therapy (n=13) and G5 after therapy (n=11). The samples were centrifuged and measured. The supernatant was obtained and stored at -80° C until assayed. Salivary EGF content was measured with a commercial ELISA kit (Quantikine, R & D Systems, Minneapolis, MN, E.U.A.). The salivary flow means to G1, G2, G3, G4, G5 were 1,27; 1,58; 1,70; 0,77 and 0,99 ml/min. respectively. Differences on salivary flow did not reach statistical significance in the groups (p=0,064) but there was a strong reduction in G4 and G5. In relation to EGF levels, it was seen 1624,08; 1816,63; 1905,47 and 1457,12 pg/ml, respectively. There was no significant difference in the salivary EGF levels of this patients (p=0,686) but the decreased levels in G4 was evident. There was a positive correlation between salivary flow and EGF levels in G4 and G5, but it was not statistically significant, G4 (p=0,446) and G5 (p=0,258). There was not association between EGF concentration and oral mucositis development (p=0,037), but it was significant between decreased salivary flow and mucositis (p< 0,001). It was shown that EGF levels were not influenced for the use of alcohol (p=0,792), tobacco (p=0,706) and the patient performance status (p=0,213). It was possible to conclude that radiation therapy induces reduction in salivary flow and EGF levels over time. That EGF levels decreased is influenced by low salivary flow, but there was no association between oral mucositis development and salivary EGF levels.